Beyond the gift: unveiling the impact of donor-recipient relationship on donors’ quality of life and mental health – results of a european bi-center study - Christina Papachristou; Natalia Papoulaki; Entela Kondi; Klemens Budde; Xavier Torres; Nina Babel; Ignacio Revuelta (Transplant International, 2026)
While living kidney donation is considered safe and beneficial, long-term psychosocial donor outcomes remain under-explored, particularly regarding donor-recipient relationships and caregiving dimensions. This study examined quality of life (QoL) and psychological outcomes among 713 living kidney donors from two major European transplant centers, assessing QoL, anxiety, depression and somatization alongside donor-recipient relationship types, caregiver role, caregiving burden and perceived responsibility for the recipient’s health. After adjusting for gender, age, center and time since donation, relationship type was not associated with physical wellbeing, but was linked to lower mental wellbeing in spouse donors compared to child-to parent and other genetically related donors. Caregiver role was linked to lower mental wellbeing and increased anxiety, caregiving burden with higher somatization, and perceived responsibility for recipient’s health with higher depression. Identified differences in mental health between centers likely reflect cultural and organisational characteristics, while differences in wellbeing linked to older age and time since donation are eventually understood within ageing processes. Conclusively, caregiving burden and perceived responsibility for the recipient’s health emerged as key predictors of psychological distress, while the effect of relationship type on wellbeing remains inconclusive. While most donors demonstrate good psychosocial outcomes, at-risk subgroups warrant appropriate attention prior and after donation.